Mosque-Based Islamic Transmission: Historical Tracks of Diponegoro and KH. Hasyim Asy'ari in the Cemetery of Kediri - Rafli, Mohammad; Susri, M. Erlin; Rochimah, Nur (JUSPI (Jurnal Sejarah Peradaban Islam), 2024)
The Kapurejo Salafiyah Mosque and Islamic Boarding School are proof of the transmission of the spread of Islam by Diponegoro and KH. Hasyim Asy'ari, founder of the Indonesian Islamic community organization Nahdlatul Ulama (NU). The mosque is a symbol of Islamic culture as a place of worship, education and social activities. The aim of this study is to examine the history of mosque-based Islamic transmission by tracing the historical traces of Diponegoro and KH. Hasyim Asy'ari in Pagu Kediri. This type of research uses qualitative research with descriptive analysis methods. The results obtained are that the An Nur Kapu mosque was once a simple mosque founded by Hasan Muhyi, a follower of Diponegoro during the Java War. The langgar was converted into a mosque after KH's wedding. Hasyim Asy'ari with Hasan Muhyi's daughter, Nyai Masruroh. After Diponegoro's arrest, a Kyai follower used the An Nur Kapu Mosque as a base to spread Islam in the Kapu area, Kediri. Diponegoro's followers spread and established mosques and Islamic boarding schools as a base for resistance outside Dutch control. Several ancient Islamic boarding schools in East Java together changed the focus of the struggle from physical conflict to education. KH Hasyim Asy'ari carried out reforms, especially in the field of education, by implementing education that had a more structured system. The strategy of the kyai and the An Nur Kapu mosque in spreading Islam is to provide teaching and learning systems that are in accordance with the culture of the community.